Teachers’ Perceptions: The Benefits and Weaknesses of Local and Foreign Cultural Representation in English Textbooks in Indonesia - Shella Monica; Muhammad Kristiawan; Azizatul Khairi; Sudarwan Danim (STAI Hubbulwathan Duri, 2023)
Language and culture cannot be separated. Cultural integration in ELT now becomes the focus of many researchers and trends in recent years. Unfortunately, so far, there has been no in-depth investigation that focused on Indonesian teachers' perceptions of local and foreign cultural presentations in high school English textbooks. To fill the gap, this study aims to investigate the teachers' perception of the benefits and weaknesses of local and foreign cultural representation (LCFR) in the ELT textbook they used. This study uses a qualitative approach with a descriptive method. The nine senior high school teachers representing the city, district, and province in South Sumatra, Indonesia, were purposely involved as the participant in this study. A semi-structured interview supporting documentation was conducted and analysed following the interactive model of data analysis proposed by Miles and Huberman. Based on the findings, there are three main benefits of LCFR in ELT textbooks; first, LFCR helps teachers stimulate or catch students’ attention at the beginning of the teaching process. Second, it improves students’ intercultural knowledge, be aware of a different cultures from other countries, and avoids culture shock. Next, it also increases students’ curiosity and critical thinking, making the learning process more active and meaningful. Moreover, the weaknesses are dealing with the imbalanced portion of cultural representation and inadequate information on cross-cultural understanding which cause misunderstanding and confusion for the students.